Exigências térmicas do fungo cultivado por formigas cortadeiras do gênero Acromyrmex Mayr, 1865 (Hymenoptera, Formicidae) - Freitas, Deise Farias (2010)
Leaf-cutting ants belonging to Attini (Hymenoptera-Formicidae-Myrmicinae), especially the genus Acromyrmex, are among the worst pests of Brazilian agriculture, because plants and cut pieces to carry inside their nests. The plant material is used for growing Leucoagaricus gongylophorus (Singer), from which they feed. The study aimed to determine the optimal temperature for growth and development of the symbiotic fungus Leucoagaricus gongylophorus (Singer). The fungi used in the study come from three different species of leaf cutting ants: Acromyrmex ambiguous (Emery, 1887), Acromyrmex crassispinus (Forel, 1909) and Acromyrmex heyeri (Forel, 1899), that these fungi were isolated and layered on Petri dishes containing culture medium SILVA-PINHATI et al. (2005). The treatments used were the temperatures 15, 18, 22, 25, 28 and 30ºC, which evaluated the halo of growth of the fungus 63 days after its establishment in the culture medium. The experimental design was randomized, and for each temperature were 20 repetitions. Data were analyzed by the MOBAE program. The value of the lower development threshold temperature (Tb) for the symbiotic fungus L. gongylophorus cultivated by the species A. ambiguus, were 16.22ºC, for the period studied with excellent development thermal threshold between 19.39ºC and 21.02ºC. The model adopted did not set the fungi cultivated by A. crassispinus and A. heyeri, showing that the temperature ranges adopted were not appropriate for those species, thus revealing different thermal requirements.